Diseño del proyecto de expansión de la empresa "Granja Nacional" al sector periférico de la ciudad de Quito. - Cerón Ruales, Wendy de las Mercedes (2006)
This research is conducted in order to determine the operating structure that ensures expansion "National Farm" and based on a study to identify the elements to increase sales and expand into other territory by strengthening the opportunities and strengths and benefit from our own weaknesses and threats to meet our target market and to improve as a company.